Delivery of Vaccines via the Nasal Route - Amponsah, S.K.; Amoafo, E.B. (Springer Link, 2023)
Several methods, including novel formulations and production systems, have been proposed as ways to improve drug delivery. Nasal delivery of drugs is traditionally employed when local effects (allergies, congestion, and respiratory illnesses) and/or systemic effects (pain treatment) are required. Over the last couple of years, the nasal route has been sought as a site for vaccine delivery. Data suggests that when vaccines are administered via the nasal route, they elicit powerful immune system responses. There are a number of vaccines that have been developed for nasal administration, some of which include Nasalflu, FluMist®, and Coronavac, among others. The nasal route for delivering vaccines has many merits; however, a few drawbacks limit the use of this route. Nonetheless, scientists are still trying to exploit this route as a potential for vaccine administration.
Research Article
Keywords: Absorption; Liposomes; Mucociliary; Nasal delivery; Vaccine